2016
DOI: 10.1177/0011392115618731
|View full text |Cite
|
Sign up to set email alerts
|

Transforming feminicidio: Framing, institutionalization and social change

Abstract: This article analyses the transformation of femicide from an academic concept into a frame for political struggle, and into a crime in the context of Mexican feminist activism against the murders of women, or feminicidios, in Ciudad Juárez and Chihuahua City. Through analysis of interviews with Mexican activists, the author argues that the implications of the transformations of feminicidio for social change are tied to the interplay between the transnational and the local impacts of feminist human rights advoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The various responses of nation-states to femicide/feminicide have been the focus of increasing international attention, especially in Latin America, where countries tend to have higher rates of femicide (Aikin, 2011;Dawson, 2015;Fregoso and Bejarano, 2010;García-Del Moral, 2015;Laurent et al, 2013;Muñoz, 2011). Eriksson et al (2005) draw upon research from Denmark, Finland, Sweden, and Norway, to examine how men's violence in families is perceived and addressed in the Nordic context.…”
Section: Violence Against Women and The Statementioning
confidence: 99%
“…The various responses of nation-states to femicide/feminicide have been the focus of increasing international attention, especially in Latin America, where countries tend to have higher rates of femicide (Aikin, 2011;Dawson, 2015;Fregoso and Bejarano, 2010;García-Del Moral, 2015;Laurent et al, 2013;Muñoz, 2011). Eriksson et al (2005) draw upon research from Denmark, Finland, Sweden, and Norway, to examine how men's violence in families is perceived and addressed in the Nordic context.…”
Section: Violence Against Women and The Statementioning
confidence: 99%
“…I found that it was mainly feminist legislators who gave gendered discursive significance to the failure of state institutions and actors, federally and locally, to respond to this violence. Taking into consideration my previous work on the construction of feminicidio as a frame in the context of transnational activism (García-Del Moral 2016), in a second round of coding I focused on how feminists understood the state responsibility for feminicidio . I paid attention to how they mobilized narratives of modern statehood to legitimate their legislative goal of criminalizing feminicidio and passing the General Law on Women’s Access to a Life Free of Violence.…”
Section: Methodsmentioning
confidence: 99%
“…The transnational advocacy network used the reports to “name and shame” Mexico, undermining its status in the international community, and to pressure it into changing practices toward gender violence (Aikin Araluce 2011; García-Del Moral and Neumann 2019). As part of this process, activists turned feminicidio into a frame accusing the Mexican state of violating women’s human rights (García-Del Moral 2016).…”
Section: Feminicidio Transnational Feminist Activism and The Mexicamentioning
confidence: 99%
“…Since the 1990s, feminist grassroots activists began to organize transnationally against the disappearance and brutal murder of hundreds of young women in Ciudad Juárez (Aikin Araluce , , ; Anaya Muñoz ). Through the feminist scholarship and activism of Marcela Lagarde and Julia Monárrez, these murders and the impunity that characterized them were framed as feminicidio (Aikin Araluce ; García‐Del Moral ). Activists aimed not only to name and shame the state for its impunity, but also to hold it responsible for violating its obligations under the Belém Do Pará Convention and the CEDAW using legal strategies involving the Inter‐American system and the CEDAW Committee under OP‐CEDAW (García‐Del Moral ).…”
Section: Criminalizing Feminicidio In Mexicomentioning
confidence: 99%